Research on dynamic characteristics of wind turbine hybrid towers under environmental influences based on operational modal identification and refined finite element simulation - Xing, Kankan; Zhang, Zhenli; Tang, Shengbo; Jiang, Weitao; Lacidogna, Giuseppe; Xu, Jie (Frontiers in Built Environment, 2026)
As hybrid towers of wind turbines have gradually become the mainstream structural configuration for high-power wind turbines, their structural safety and long-term reliability have increasingly become critical issues. However, existing studies have insufficiently focused on the impacts of environmental factors and local structural characteristics on hybrid tower structures. To address this gap, this study conducts research on the dynamic characteristics of wind turbine hybrid towers based on Operational Modal Analysis (OMA) and finite element simulation. This study proposes a systematic operational modal analysis process: compared with traditional modal identification methods, this study combines the Frequency Domain Decomposition (FDD) method and the Stochastic Subspace Identification-Covariance (SSI-COV) method to achieve effective extraction of structural modal frequencies and mode shapes under operational conditions. Through the progressive strategy of preliminary identification-accurate estimation-spurious mode elimination, this process significantly improves the efficiency and accuracy of modal parameter identification. The analysis results show that within the range of conventional environmental variations, no significant statistical correlation is observed between the identified modal parameters (frequency, mode shape) and environmental factors (wind direction, wind speed, temperature). It should be noted that the validity of these conclusions is limited to the specific environmental conditions and data acquisition periods investigated in this study—namely, wind speeds of 2.0–5.5 m/s, temperatures of 17 °C–35.8 °C, wind direction variations of approximately 10°, and data collected daily between 11:45 and 12:15—without encompassing seasonal-scale extreme environmental variations. Meanwhile, this study establishes a finite element model of the wind turbine hybrid tower and verifies its effectiveness using on-site measured data. Parametric analysis and damage simulation based on the validated model reveal that the elastic modulus of concrete is the most sensitive parameter affecting the overall dynamic characteristics of the structure, compared with the elastic moduli of steel and foundation. Additionally, the influence of stiffness degradation in different regions of the concrete tower on the natural frequencies of each order is related to the specific location of damage and the modal order of structural vibration. The conclusions of this study provide a theoretical basis for the optimal design of wind turbine hybrid tower structures and offer important references for formulating structural health monitoring strategies based on dynamic characteristics.